Comparison of allometric equations and biomass expansion factors for six evergreen broad-leaved trees in subtropical forests in southern Korea. (3rd April 2019) - Kim, Choonsig; Baek, Gyeongwon; Yoo, Byung Oh; Jung, Su Young; Lee, Kwang Soo; An, Ki Wan
ABSTRACT: This study was conducted to compare the allometric equations and biomass expansion factors (BEFs) of six dominant evergreen broad-leaved trees ( Camellia japonica L, Castanopsis sieboldii Hatus, Quercus acuta Thunb, Q. glauca Thunb, Machilus thunbergii S. et Z., and Neolitsea sericea Koidz) in subtropical forests. A total of 86 trees were destructively sampled to quantify the aboveground biomass of each tree component (i.e., leaves, branches, and stem). Species-specific or generalized allometric equations and species-dependent BEFs were developed for each tree component of the six broad-leaved forest trees. Species-specific allometric equations were significant (P < 0.05), with the diameter at breast height (DBH) accounting for 68–99% of the variation, whereas generalized allometric equations explained 64–96% of the variation. The values of stem density ranged broadly from 0.49 g cm −3 for C. sieboldii to 0.79 g cm −3 for Q. glauca, with a mean value of 0.68 g cm −3 . The BEFs were significantly (P < 0.05) lower for C. sieboldii (1.25) than for M. thunbergii (2.02). Stem density and aboveground BEFs had a significant negative relationship with tree ages. The results indicate that species-specific allometric equations and species-dependent BEFs are applicable for obtaining accurate biomass estimates of subtropical evergreen broad-leaved forests.